PENGARUH HUJAN TERHADAP PRODUKSI TANAMAN KELAPA SAWIT DI PT. PERKEBUNAN NUSANTARA V KEBUN TANDUN - Sari, Rizki Jaenita; Ardian, Ardian; Syafrinal, Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Water availability is a major factor limiting the production rate of oil palm plantations. Availability of water for palm oil plants in the field is obtained from rainfall. The research was conducted at PT. Perkebunan Nusantara V Tandun Estate, Riau Province, for three months starting in June until August 2016. This study uses secondary data available on the administration of the garden. Secondary data for analysis include TBS monthly production data for 5 years (2011-2015), the data age of the plant 5, 10 and 20 years after planting, rainfall data and rainy day for 9 years (2007-2009). The analytical method used is analasis multiple linear regression and correlation models tested for feasibility with the classical assumption test including normality test, heteroscedasticity test and multicollinearity test. Regression analysis showed that variable rainfall and rainy days significantly affected on alpha 1% (Sig <α 0,01) to FFB production at the age of 5 years. Results F-count of 29.07 with a significance value of 0.00. The coefficient of determination (R2) obtained 63.8%. This means that 63.8% of FFB production variations can be explained by the variation of the variables used and the remaining 36,2% is explained by the other variables not incorporated into the model. Regression analysis equation on a 5-year-old plant was Y = 414633.827 + 2530.523 X1 - X2 21848,726. Results of correlation analysis at 5 years old plants showed variable rainfall and rainy days have a very strong relationship. Correlation value of rainfall and rainy days and 0.720 - 0.543.Keywords: rainfall, raining, FFB production.